A new hope? Possibilities of therapeutic IgA antibodies in the treatment of inflammatory lung diseases - Bohländer, Fabian (Frontiers in Immunology, 2023)
Inflammatory lung diseases represent a persistent burden for patients and the global healthcare system. The combination of high morbidity, (partially) high mortality and limited innovations in the last decades, have resulted in a great demand for new therapeutics. Are therapeutic IgA antibodies possibly a new hope in the treatment of inflammatory lung diseases? Current research increasingly unravels the elementary functions of IgA as protector against infections and as modulator of overwhelming inflammation. With a focus on IgA, this review describes the pathological alterations in mucosal immunity and how they contribute to chronic inflammation in the most common inflammatory lung diseases. The current knowledge of IgA functions in the circulation, and particularly in the respiratory mucosa, are summarized. The interplay between neutrophils and IgA seems to be key in control of inflammation. In addition, the hurdles and benefits of therapeutic IgA antibodies, as well as the currently known clinically used IgA preparations are described. The data highlighted here, together with upcoming research strategies aiming at circumventing the current pitfalls in IgA research may pave the way for this promising antibody class in the application of inflammatory lung diseases.